2019
DOI: 10.32098/mltj.02.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein signaling in rotator cuff muscle atrophy and fatty infiltration

Abstract: Conclusion: this result suggests that BMP signaling inhibits RC muscle atrophy but promotes fatty infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…In humans, it is theorized that injury to the rotator cuff creates increased tension on the suprascapular nerve, which places the nerve at risk for injury 28 . This is a different mechanism of injury to the nerve than is seen clinically in rotator cuff tears; however, this mouse model has been shown to mimic pathophysiologic changes seen after a rotator cuff injury in previous studies 18,29 . In summary, results from this study suggest that Tie2 + progenitor cells are the major source of fibroblasts and FAPs are the major cellular source of adipocytes in RC muscle following tendon tears.…”
Section: Discussionmentioning
confidence: 97%
“…In humans, it is theorized that injury to the rotator cuff creates increased tension on the suprascapular nerve, which places the nerve at risk for injury 28 . This is a different mechanism of injury to the nerve than is seen clinically in rotator cuff tears; however, this mouse model has been shown to mimic pathophysiologic changes seen after a rotator cuff injury in previous studies 18,29 . In summary, results from this study suggest that Tie2 + progenitor cells are the major source of fibroblasts and FAPs are the major cellular source of adipocytes in RC muscle following tendon tears.…”
Section: Discussionmentioning
confidence: 97%
“…Five fields of view were analysed per sample to determine the percentage of muscle fibre coverage, as determined by the percentage of pink staining fibres in the field of view. This was performed using the Image J software; images were first converted to 8 bit, followed by thresholding and manual image adjustment to accurately measure muscle coverage area [35].…”
Section: Histological Evaluationmentioning
confidence: 99%
“…Canonical TGFβ and BMP pathway share the common downstream Smads factors, although TGFβ prefers Smad2/3 and BMP prefers Samd1/5/8 43 . Our previous studies have shown two important TGFβ and BMP family members—TGFβ‐1 9 and BMP‐7 10 are overexpressed in muscle after RC injury. In this study, we showed that TGFβ‐1 suppresses FAP adipogenesis while BMP‐7 promotes FAP adipogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Transforming growth factor beta (TGFβ) and bone morphogenetic protein‐7 (BMP‐7) have been found to play important roles in stem cell adipogenesis 8 . In our previous studies, we observed significantly increased TGFβ and BMP‐7 during the development of muscle fatty infiltrated after RC tears 9,10 . Inhibition TGFβ and BMP pathways decrease RC muscle FI after massive tendon tears 11 .…”
Section: Introductionmentioning
confidence: 94%